Conductivity, light responsive and thermal behavior of 4-methoxy-4-oxyazobenzene decyl methacrylate polymer membrane: article - Fauzi, Farah; M. Alauddin, Sakinah (2019)
The new ionically polymers have designed containing azobenzenes, sulfonic acid groups and methyl methacrylate. The 4-methoxy-4-oxy azobenzene decyl methacrylate and 4-methoxy-4oxy azobenzene decyl methacrylate-co-poly[2-acrylamido-2-methyl-propane sulphonic acid]-copoly[methyl methacrylate] were characterized by DSC,TGA,EIS and UV-VIS. The polymers have light responsive properties and liquid crystalline properties when characterized.